Projeto Ateliê de Canto em Grupo: o olhar docente sobre a formação musical na Rede Pública - Reginato, Daniel (2019)
The present study aims to investigate the advances and challenges of the teaching of arts, especially music, in the context of public schools, starting from the legal predispositions that regulate and stimulate this practice, to the reading of the existing context in the classroom and its agents. It also aims to discover the contributions of musical practice to the development of students from the teacher perspective analyzed in the case study of the "Ateliê de Canto em Grupo" - an annual project of musical formation of the Project Ateliê-Escola, working in public schools in the southern region of São Paulo. For this, it makes use of a qualitative approach in methodology with classroom teachers who followed the activities of the Ateliê de Canto with their respective classes. Through semi-structured questionnaires with these subjects it were collected perceptions of these teachers concerning the transformations of their students during this immersion process to an annual musical project. Through the analysis of their testimonies and the confrontation with the ideas present in the theoretical foundation of the teaching of arts proposed by Elliot EISNER and the curricular changes in Arts that rules for music teaching in schools, it is intended to discuss the curricular issues and teacher training for a better use of the teaching of Arts in public schools